PERANCANGAN APLIKASI TRANSLATOR BAHASA INDONESIA KE BAHASA INGGRIS ESP (ENGLISH FOR SPECIFIC PURPOSE) KOMPUTER SAINS UNTUK PENINGKATAN INFORMASI MAHASISWA MENGGUNAKAN BRUTE FORCE METHOD - Waruwu, Fince Tinus; Ramadhani, Putri (STMIK Budi Darma, 2018)
Translator is a tool to assist in translating a language from another language. Translator is very useful for tourists when traveling to other countries or other regions that do not understand the language of the country or area visited. Translator is also very useful for a student or student to learn and add knowledge about foreign languages that are not understood. The availability of translators in a university to improve services for students or those who need them. Students dont all understand foreign languages. String matching is a search technique in a text that is often called string search. String matching is often used in text search, location search, dictionary and so on. String matching has several algorithms, including brute force, boyer moore, knuth morris pratt and many more algorithms contained in string mathing. The Indonesian to English translator application uses the string mathing brute force algorithm. Brute force algorithm is matching each character from left to right.Keywords: Translator, String Matching, Algorithm, Brute Force